Formulasi Sediaan Lipbalm dari Ekstrak Biji Kopi Arabika (Coffea Arabica L.) Java Preanger Sebagai Emolien - Retty Handayani (Jurnal Ilmiah Farmasi Farmasyifa, 2021)
Lipbalm preparations are a decorative cosmetic dosage form for moisturizing lips. One of the most important components of lipbalm preparations is an emollient. Emollients work by covering the damaged skin with beads of fat so that the skin of the lips becomes softer and moisturized. Arabica coffee beans (Coffea arabica L.) java preanger contain linoleic acid which functions as an emollient. This study aims to make a lipbalm formulation containing extracts of Arabica coffee beans (Coffea Arabica L). Lipbalm preparations made with variations in the concentration of coffee extract 3%, 6% and 9%. The resulting formula is then evaluated for its physical stability. The irritation test is carried out using the patch test method, testing the effectiveness of emollients using a skin analyzer. The results showed that variations in the extract of coffee used (3%, 6% and 9%) showed that the concentration of 9% was more stable. The irritation test results show that all three formulas are safe to use. Based on the results of the effectiveness test shows that the formula with a concentration of 9% gives a good emollient effect after use based on statistical tests the paired samples T-test method.Keywords : emollients, coffee bean extracts, formulation, lipbalm.